Linking financial incentives idiosyncratic deals with unethical pro-organizational behaviors in pharmaceutical companies: The mediating role of reflective moral attentiveness - Abdul Rauf Qureshi; Basharat Raza (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
The purpose of this study is to investigate the mediating role of reflective moral attentiveness in the relationship between financial incentives idiosyncratic deals and unethical pro-organizational behaviors in the pharmaceutical sales sector. In this study, data collected from 310 sales managers in pharmaceutical companies in Pakistan was analyzed using structural equation modeling (SEM) in SPSS version 23. The study found significant positive relationship between financial incentives idiosyncratic deals and unethical pro-organizational behaviors whereas reflective moral attentiveness statistically mediates between this positive relationship. The study is the first to describe the role of reflective moral attentiveness in the relationship between financial incentives idiosyncratic deals and unethical pro-organizational behaviors in pharmaceuticals sales sector of Pakistan. The findings of the study have been discussed in detail, including important practical and theoretical implications, limitations, and future directions.
Keywords: 330; reflective moral attentiveness; unethical pro-organizational behaviors; financial incentives idiosyncratic deals; pharmaceutical companies